2010
DOI: 10.1039/b915589a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the hydrophobicity and electrospray response of glycans through derivatization with novel cationic hydrazides

Abstract: Novel tags are used to increase the hydrophobicity of glycans and impart a permanent charge yielding as great as a approximately 5-fold increase in electrospray response from both a standard and complex mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 20 publications
2
66
0
Order By: Relevance
“…Researchers have been hesitant to incorporate a permanent charge hypothesizing that it would have a negative effect in the fragmentation patterns of the glycans and could cause partial or total loss of the tag 18 . Recently, though, it has been shown that CID fragmentation patterns of a charged complex glycan are not negatively affected by a permanently charged tag nor is the tag lost during fragmentation 29 . Given these results, charged hydrazide reagents are now considered a viable avenue toward the hydrophobic tagging of glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been hesitant to incorporate a permanent charge hypothesizing that it would have a negative effect in the fragmentation patterns of the glycans and could cause partial or total loss of the tag 18 . Recently, though, it has been shown that CID fragmentation patterns of a charged complex glycan are not negatively affected by a permanently charged tag nor is the tag lost during fragmentation 29 . Given these results, charged hydrazide reagents are now considered a viable avenue toward the hydrophobic tagging of glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Two related derivatives prepared from the 4-phenyl pyridine (108) and the tripropylamino-analogue of Girard's T reagent (109) have been prepared and examined by HILIC nano-LC/MS [248]. Both derivatives but particularly the tripropylamino-analogue, produced an increase in sensitivity but, unlike the earlier reports, the sensitivity of the Girard's T derivative of maltoheptaose was lower that that from the unlabelled carbohydrate.…”
Section: Hydrazonesmentioning
confidence: 94%
“…Hydrophobic tagging has demonstrated great potential to dramatically increase the utility of MS-based proteomics by improving the detectability of derivatized peptides and proteins and, more recently, has even shown promise for the ana lysis of glycans [33,34]. However, based on the studies to date, it is clear that no universal reagent exists that will positively impact the characterization of an entire proteome and, thus, future applications of hydrophobic tagging are expected to remain focused on targeted analyses for which an optimal reagent can be determined.…”
Section: Five-year Viewmentioning
confidence: 99%